If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Bx + My = Z Solving xB + yM = Z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1yM' to each side of the equation. xB + yM + -1yM = Z + -1yM Combine like terms: yM + -1yM = 0 xB + 0 = Z + -1yM xB = Z + -1yM Divide each side by 'B'. x = B-1Z + -1yB-1M Simplifying x = B-1Z + -1yB-1M
| 5-2a=-1 | | 9-3(x)=2(x+4) | | 3v^2+4=v | | 1/4a16 | | (4a-3b)(a+2b)-(4a+3b)(a-2b)= | | 8+x-1=-1+2x | | 2+3lnx=7 | | -41x=451 | | 5-2+9=-16 | | 25-9x=1-x | | 4m-((2m+n)-(4m-7n)+(2m-8n))= | | 7-(-1-6x)=4x-8 | | -5-8=-5h+8 | | -(3x+2)=4 | | 6x-(4x+8)=4x-14 | | -108/9=9/9j | | 2=8+3y | | 3x+12=2(x-(4-x)) | | 3(s-4)+s=-5s+51 | | 3-1/5x-4 | | 4.4x=-0.8x | | 5x-2-7x=4 | | 5x+6=10x+1 | | 6(x-3)=10x | | 5-x-2=4x+3+4x+5 | | 12q=155 | | y^2-xy+3=-xy+y+y^2 | | 1=3x+11 | | -1/6y=7 | | 4x+4=5(x-4) | | 25=2y-5 | | -12=2(2-x) |